COMMUNITY READING GARDEN MANAGEMENT (TBM) MANAGEMENT IN IMPROVING WOMEN'S ECOLOGICAL LITERATION - Juhana Juhana (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2019)
The community reading park (TBM) is one of the community education institutions that has become the foundation for the development of programs to improve the quality of life of the community. Because with the presence of TBM the community will have broad access to information and cooperation networks. However, the management of this community education unit is still experiencing various obstacles, therefore it is necessary to examine the process of managing community education units, especially in the context of increasing ecological literacy for women. The theories used are empowerment theory, public education theory and environmental ecology theory. While the research method used is descriptive qualitative research method with a research source of 10 respondents, the instruments used are interview guidelines, observation guidelines and documentation studies. In the results it was found that management of TBM managers played an important role in improving ecological literacy, including supporting women's understanding in utilizing the environment to improve the quality of life. With the conclusion that the management of TBM management provides support for increasing ecological literacy for women.